Implementation of the Independent Curriculum in Improving the Quality of Education in SMA Negri 1 Belitang III - Permatasari, Pinky; Aldi, Khoirul; Nidiatika, Anggun; Maja, Gergely (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
The curriculum is the